A review of thermoelectric ZnO nanostructured ceramics for energy recovery - M A, Mohammed; Sudin, Izman; Mohd Noor, Alias; Rajoo, Srithar; M B, Uday; H. Obayes, Noor; Firdaus Omar, Muhammad (International Journal of Engineering and Technology, 2018)
The thermoelectric devices have the ability to convert heat energy into electrical energy without required moving components, having good reliability however their performance depends on material selections. The advances in the development of thermoelectric materials have highlighted to increase the technologyâ€™s energy efficiency and waste heat recovery potential at elevated temperatures. The fabrication of these thermoelectric materials depends on the type of these materials and the properties using to evaluate these kind of materials such as thermopower (Seebeck effect), electrical and thermal conductivities. Ceramic thermoelectric materials have attracted increased attention as an alternative approach to traditional thermoelectric materials.Â  From these important thermoelectric ceramic materials that can be a candidate for n-type is ZnO doping, which have excellent thermal and chemical stability, as they are promising for high temperature power generator. This review is an effort to study the thermoelectric properties and elements doping related with zinc oxide nano-ceramic materials. Effective ZnO dopants and doping strategies to achieve high electrical and thermal conductivities and high carrier concentration are highlighted in this review to enable the advanced zinc oxide applications in thermoelectric power generation.Â